2019
DOI: 10.1136/bmjopen-2019-035007
|View full text |Cite
|
Sign up to set email alerts
|

More aware, more protected: a cross-sectional study on road safety skills predicting the use of passive safety elements among Spanish teenagers

Abstract: ObjectiveThis study had two objectives: first, to test the effects of sociodemographic variables, and the effects of three key road safety skills (knowledge–risk perception–attitudes) on the use of passive safety elements (PSEs) among teenagers; and second, to assess the differential impact of the study variables on PSEs use from a gender-based perspective.Setting and participantsThis cross-sectional study was framed in the paradigm of primary care, and it involved students from several educational centres in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
(94 reference statements)
1
9
0
Order By: Relevance
“…Among the three road safety skills measured in this study, rule knowledge was the only one not exerting a direct effect on the self-rated protective behaviors of children. A similar finding was documented in the case of Spanish male adolescents by Useche et al [22], suggesting that behavioral competences a) jointly interact in the explanation of both risky and safe behaviors, and b) can also be more influenced by risk perception and attitudinal settings than by mere conceptual settings that need further processes (e.g., motivation, attitudes) to translate into action. In addition, Zeedyk et al [47] found a similar outcome, thus supporting the theory that an increased knowledge on road-related normative does not necessarily imply behavioral improvements; this is especially true in the absence of complementary skills aimed at enhancing the decision-making of children in the road environment.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Among the three road safety skills measured in this study, rule knowledge was the only one not exerting a direct effect on the self-rated protective behaviors of children. A similar finding was documented in the case of Spanish male adolescents by Useche et al [22], suggesting that behavioral competences a) jointly interact in the explanation of both risky and safe behaviors, and b) can also be more influenced by risk perception and attitudinal settings than by mere conceptual settings that need further processes (e.g., motivation, attitudes) to translate into action. In addition, Zeedyk et al [47] found a similar outcome, thus supporting the theory that an increased knowledge on road-related normative does not necessarily imply behavioral improvements; this is especially true in the absence of complementary skills aimed at enhancing the decision-making of children in the road environment.…”
Section: Discussionsupporting
confidence: 79%
“…In the case of children, and very similarly to what is observed in the positive attitudes, risk perception and rule knowledge (PARK) model, it usually focuses on improving the knowledge of road safety settings (e.g., norms, signals), the awareness on risk-increasing aspects and the self-assessment of children in their daily transportation tasks/situations. Thus, the needs identified for earlier life stages seem to be different, and they appear highly related to the integration of Education for Road Safety (RSE) in curricular activities and school-based programs that consider specificities and particular factors such as children's age, gender, personality, cognitive skills and social environment, primarily composed of e.g., parents, relatives, peers and other relevant stakeholders [7,21,22]. Actually, some studies addressing the practices related to the school-based RSE have found that, in countries such as the United States, Road Safety Education is much more developed in primary schools; here, the interventions are frequently directed by a single professor that is more involved in the activity development, which may strengthen the participation and the consistency of the interventions throughout time [10].…”
Section: Rse For Children: the Same Topic But A Different Scopementioning
confidence: 99%
See 3 more Smart Citations